2021
DOI: 10.5851/kosfa.2021.e53
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pesticide Residue in Muscle and Fat Tissue of Pigs Treated with Propiconazole

Abstract: This study estimated the effect of exposure to propiconazole through implementation and residues in finishing pigs. We analyzed the expression of fibrosis-related genes and performed histological analysis of the blood, liver, kidney, muscle, ileum, and fat tissues. The animals were exposed for 28 d to different concentrations of propiconazole (0.09, 0.44, 0.88, 4.41, and 8.82 mg/kg bw/d). Quantitative, gene expression, and histological analyses in tissues were performed using liquid chromatography mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Thus, tebuconazole treatment at different concentrations for 28 d did not affect the growth performance of pigs. These results are similar to those of other previous studies ( Jeong et al, 2021 ; Jeong et al, 2022 ; Lopez-Antia et al, 2021 ). Propiconazole and flutriafol were not significantly different between control and the treatment groups in pigs and chicks.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Thus, tebuconazole treatment at different concentrations for 28 d did not affect the growth performance of pigs. These results are similar to those of other previous studies ( Jeong et al, 2021 ; Jeong et al, 2022 ; Lopez-Antia et al, 2021 ). Propiconazole and flutriafol were not significantly different between control and the treatment groups in pigs and chicks.…”
Section: Resultssupporting
confidence: 93%
“…ALT regulates transamination and is a marker for functional damage in the liver and kidney ( Firat et al, 2011 ; Ochiai et al, 2020 ; Sookoian and Pirola, 2012 ). Previous studies have also shown that triazole fungicides (i.e., propiconazole and flutriafol) increased the ALT levels in pigs ( Jeong et al, 2021 ; Jeong et al, 2022 ). ALT levels increase ROS levels and oxidative damage ( Patil et al, 2009 ; Singh et al, 2011 ).…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations